OPTIMIZATION OF DIGITAL MARKETING STRATEGIES IN EKOWISATA MANGROVE PANDANG TAK JEMU BATAM CITY'S THROUGH SOCIAL MEDIA - Anggara, Rendhy Putra; Khairunnisa, Khairunnisa; Hafsar, Khairul (Jurnal Segara, 2025)
Indonesia is a country that has extraordinary wealth, starting from natural beauty, vegetation, fauna and culture. The natural beauty that Indonesia has is its abundant natural wealth. Indonesia's natural beauty is also widely used as a tourist attraction, one of which is mangrove tourism. Mangroves have great potential as a tourist destination because the unique beauty of mangroves can offer its own charm and uniqueness so that it can attract tourists to visit the mangrove area. To expand information related to tourist attractions, many people are marketing their tour packages through social media, making social media an opportunity to market and promote their tourism. One of the tourist attractions that uses social media as a marketing medium is Ekowisata Mangrove Pandang Tak Jemu. The aim of the research is to identify digital marketing strategies carried out by managers and formulate digital marketing strategies through social media that are best applied to the Ekowisata Mangrove Pandang Tak Jemu. The research was carried out in June – July 2024 at the Ekowisata Mangrove Pandang Tak Jemu. The research method used is descriptive qualitative using SWOT and AHP analysis. The research results show the application of digital marketing strategies through social media in Ekowisata Mangrove Pandang Tak Jemu This can be seen from the use of several social media applications, namely Instagram, Facebook and Twitter (X). Based on the results of the SWOT and AHP analysis, there are 5 priority strategies in formulating digital marketing strategies through social media on Ekowisata Mangrove Pandang Tak Jemu, namely, (1) repairing damaged infrastructure, (2) providing training for HR, (3) improving and maintaining service quality, (4) holding activity events at tourist locations.